Type II transmembrane serine proteases 4 (TMPRSS4) promotes proliferation, invasion and epithelial–mesenchymal transition in endometrial carcinoma cells (HEC1A and Ishikawa) via activation of MAPK and AKT. Issue 4 (4th July 2021) - Xiao, Huan; Zhang, Zhian; Peng, Dan; Wei, Chunqing; Ma, Benling
ABSTRACT : Endometrial cancer is the most common gynecological cancer in the developed countries. Type II transmembrane serine proteases 4 (TMPRSS4) is a newly discovered transmembrane protein, which may be related to the invasion, metastasis of the tumor and the poor prognosis. This study aims to investigate the role of TMPRSS4 in endometrial cancer and the detailed molecular mechanism. The results showed that TMPRSS4 was highly expressed in human endometrial cancer cells (HEC1A and Ishikawa). TMPRSS4 knockdown inhibited proliferation of endometrial cancer cells. In TMPRSS4 knockdown cells, the invasion of cells was significantly supressed. The expression of E-cadherin was significantly enhanced, while the levels of fibronectin and vimentin decreased in TMPRSS4 knockdown cells, which indicated thatTMPRSS4 knockdown attenuated the EMT of cancer cells. TMPRSS4 positively regulated the activation of MAPK and AKT signaling pathways in endometrial cancer. In conclusion, this study indicated that TMPRSS4 may be associated with the progression of endometrial cancer through promoting proliferation, invasion and EMT via activation of MAPK and AKT in endometrial cancer cells. TMPRSS4 may be a new and more effective target or therapeutic strategy for treating endometrial cancer.